The conversation between public theology and missiology: A response to Sebastian Kim - Fensham, Charles James (Missiology, 2017)
This paper responds, from a North American perspective, to Sebastian Kim's plenary address at the 2016 annual meeting of the American Society for Missiology on the relationship between public theology and missiology. The paper reviews the contribution of North American missiologists to the reflection on the public witness of the church, highlights the published contributions of Hunsberger, Leffel, Pieterse, Hunt, Okesson and Fensham, while recognizing the contribution of practitioners such as Kenney and Simpson. The paper proposes that missiologists can contribute to the conversation with public theologians on the themes of theologies of culture, the missionary dimension of all theology, the clarification of the meaning of church, world and publics, the theme of repentance, and offering an inspiring transformative vision for a flourishing creation.